Evaluation Of The Environmental Performance Of Industrial Companies Operating In Lattakia Governorate - يمن منصور; أحمد علي قوزي (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The aim of the research is to assess the environmental performance of industrial companies operating in Lattakia Governorate using the data of the ISO14001 standard, represented by the variables (environmental policy, planning, implementation and operation, environmental management system, environmental management tools and environmental performance dimensions). Theoretical, as the statistical survey method was used, where the researcher distributed (140) questionnaires to a sample of industrial companies operating in the Lattakia governorate under study, (137) questionnaires that fulfilled the research conditions were retrieved which represent (98%) of the distributed questionnaires. The researcher also analyzed the data by using the statistical analysis program (SPSS.23). At the end of the research, the researcher reached a set of conclusions, the most important of which are: The actual environmental performance of the industrial companies under study does not correspond to the required environmental performance, where the statistical analysis of the data showed that all environmental performance variables except for the “planning” variable were below the required level, which indicates that the industrial companies under study does not take the environmental aspect seriously into consideration in its various activities. The researcher also made several recommendations, the most important of which are: The industrial companies operating in Lattakia Governorate should focus on developing a specific environmental policy with clear goals and objectives, in addition to setting up an environmental management system that integrates with other systems of companies, both administrative and financial, and the concerned authorities in the country must impose conditions on industrial companies to obtain international ISO certificates related to the environment or other equivalent certificates.